The Effect of Cloud-Based Point of Sale (Pos) Technology on the Speed and Accuracy of Accounting Information Systems in Micro, Small, And Medium Enterprises (MSMEs) - April Lianingsih; Loggar Bhilawa (Universitas KH. Abdul Chalim Mojokerto, 2026)
Indonesian MSMEs face inequality in the adoption of accounting technology which causes reporting delays and a high risk of recording errors. This study aims to analyze the effect of the ease of use and usability of cloud-based POS on the speed and accuracy of the Accounting Information System (SIA), as well as the role of digital competence as a moderation variable. Data were collected through a Likert scale questionnaire of 1–4 to 100 F&B MSME respondents in Surabaya using purposive sampling, analyzed by multiple linear regression and Moderated Regression Analysis (MRA). The results showed that the ease of use (sig. 0.000) and usability (sig. 0.000) of cloud POS had a positive and significant effect on the speed and accuracy of SIA. Digital competence was proven to strengthen both influences (sig. 0.009 and 0.040), with an Adjusted R Square of 50.1%. MSME actors are advised to increase digital literacy so that the benefits of cloud POS can be optimized.